2016
DOI: 10.1186/s12974-016-0476-z
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of bee venom phospholipase A2 in the 3xTg AD mouse model of Alzheimer’s disease

Abstract: BackgroundAlzheimer’s disease (AD) is a severe neuroinflammatory disease. CD4+Foxp3+ regulatory T cells (Tregs) modulate various inflammatory diseases via suppressing Th cell activation. There are increasing evidences that Tregs have beneficial roles in neurodegenerative diseases. Previously, we found the population of Treg cells was significantly increased by bee venom phospholipase A2 (bvPLA2) treatment in vivo and in vitro.MethodsTo examine the effects of bvPLA2 on AD, bvPLA2 was administered to 3xTg-AD mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 65 publications
1
68
0
Order By: Relevance
“…The 3×Tg mice exhibit a regional and age-dependent enhancement of F4/80-positive (Janelsins et al, 2005), IBA1-positive (Montgomery et al, 2011), and CD11b-positive microglia (Ye et al, 2016). The phenomenon is associated with amplification of various factors of inflammation in the brain, including TNFα (Montacute et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…The 3×Tg mice exhibit a regional and age-dependent enhancement of F4/80-positive (Janelsins et al, 2005), IBA1-positive (Montgomery et al, 2011), and CD11b-positive microglia (Ye et al, 2016). The phenomenon is associated with amplification of various factors of inflammation in the brain, including TNFα (Montacute et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…The therapeutic effect of bvPLA2 extends to the treatment for neurodegenerative diseases including AD [32]. Previous studies demonstrated the neuroprotective effect of bvPLA2 against Parkinson's Disease [33] and AD [9]. The main action of bvPLA2 on a cellular level is the suppression of immune responses through the stimulation of dendritic cells, which ultimately leads to an increased function of Treg cells [20].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, bvPLA2 is a potent inducer of T helper type 2 (Th2) immune reactions and the activation of group 2 innate lymphoid cells (ILC2) through the release of IL-35 [7]. Recently, numerous studies have reported the protective effects of bvPLA2 against a variety of diseases, including Alzheimer's disease, allergic asthma, and cisplatin-induced organ inflammation [8][9][10]. Chung et al revealed that bvPLA2 binds to a mannose receptor (CD206) or a C-type lectin on dendritic cells (DC) and increases the expression of prostaglandin E2 (PGE2), which binds to EP2 receptors on naïve T helper cells and leads to the differentiation into CD4 + CD25 + Foxp3 + regulatory T cells (Tregs) [11].…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, transient depletion of Tregs in mouse models of AD accelerates the onset of cognitive deficits; conversely, amplification of Tregs improves cognitive functions (165). Therefore, increased frequency and suppressive activities of Tregs within AD patients suggest a protective role in autoimmune disorders (166,167).…”
Section: Amyloid β and Regulatory T Cellsmentioning
confidence: 92%